Analysis of misalignment grave in Kampung Sungai Baru cementry area using [GIS] / Mohd Fairul Afiq Mohd Zulkefli - Mohd Zulkefli, Mohd Fairul Afiq (2018)
Nowadays, the usage of digital mapping has increased the uses and advantages of various kind of analysis and data collection methods. However, usage of digital mapping in cemetery areas are rare in Malaysia. Grave mapping seems does not seem to be taken seriously in any religion in Malaysia, although mapping is beneficial in many aspects. Action should be taken to create awareness and identify which part of any particular Muslim cemetery which has strayed from the Qiblah direction. The aim of this study is to determine the alignment of graves at the cemetery area of the Ameer Fawwaz Mosque in Kampung Sungai Bharu, Perlis. This research was conducted with the objectives: i) to spatially map the existing grave plot based on orthomosaic images, ii) to evaluate the percentage of Muslim graves in the Exact Direction, In Allowable Tolerance and Strayed categories iii) to classify the adjusted value of the Qiblah for the misaligned graves that do not adhere to the direction of the Qiblah. The orientation and position of graves were identified through orthomosaic photos acquired from the interpretation of Unmanned Aerial Vehicle (UAV) image in the Pix4Dand ArcGIS software. After the map is produced it would identify the percentage of misaligned graves and adjusted value for the misaligned graves. The results would indicate how good or poor the determination of Qiblah direction for the cemetery area itself.